2022
DOI: 10.1093/jn/nxac204
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Genetic Determinants of Plasma Inositol Status in Adult Humans

Abstract: Background Myo-inositol (MI) is incorporated into numerous biomolecules, including phosphoinositides and inositol phosphates. Disturbance of inositol availability or metabolism is associated with various disorders, including neurological conditions and cancers, while supplemental MI has therapeutic potential in conditions such as depression, polycystic ovary syndrome and congenital anomalies. Inositol status may be influenced by diet, synthesis, transport, utilisation and catabolism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The potential for a genetic component in the regulation of circulating MI was investigated in a genome‐wide association study in healthy young adults. This study revealed a nominally significant association of plasma MI with SLC5A11 , encoding a sodium‐coupled inositol transporter (SMIT2), and suggestive association with three other genes 22 . However, lack of association of genome‐wide significance suggested that plasma MI is strongly influenced by non‐genetic factors such as diet.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…The potential for a genetic component in the regulation of circulating MI was investigated in a genome‐wide association study in healthy young adults. This study revealed a nominally significant association of plasma MI with SLC5A11 , encoding a sodium‐coupled inositol transporter (SMIT2), and suggestive association with three other genes 22 . However, lack of association of genome‐wide significance suggested that plasma MI is strongly influenced by non‐genetic factors such as diet.…”
Section: Introductionmentioning
confidence: 78%
“…For example, among mice maintained on the standard diet in this study, the mean plasma MI of approximately 69 μM was approximately double the mean value of 28 μM that we observed in a population of young healthy adults. 22 In considering MI deficiency as a potential risk factor for NTDs, serum MI concentration has been determined among mothers and their infants with spina bifida. Although, a relatively small-scale study, there was a non-significant difference in mean values between NTDs and controls but the lowest decile of maternal MI values was significantly associated with having a child with spina bifida.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations